2015
DOI: 10.1002/clc.22404
|View full text |Cite
|
Sign up to set email alerts
|

Increased Transforming Growth Factor‐β Levels Associated With Cardiac Adverse Events in Hypertrophic Cardiomyopathy

Abstract: Background: Hypertrophic cardiomyopathy (HCM) is a common genetic heart disease characterized by ventricular hypertrophy, myocardial fibrosis, and impaired ventricular relaxation. The exact mechanisms by which fibrosis is caused remain unknown. Hypothesis: Circulating TGF-β is related to poor prognosis in HCM. Methods: We compared TGF-β levels of 49 HCM patients with those of 40 non-HCM patients. We followed the patients with HCM for 18 months and divided them into 2 groups: low TGF-β (≤4877 pg/mL) and high TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 40 publications
(50 reference statements)
2
17
0
1
Order By: Relevance
“…Dynamic changes in the ECM occur following AMI and has an important role in ventricular remodeling. During the period of AMI, transforming growth factor in cardiac muscle tissue of TGF-β promoting fibrosis factor is activated (21). The fibrosis cell generates into type I and type III collagenous fibers, which gradually develop into scar tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic changes in the ECM occur following AMI and has an important role in ventricular remodeling. During the period of AMI, transforming growth factor in cardiac muscle tissue of TGF-β promoting fibrosis factor is activated (21). The fibrosis cell generates into type I and type III collagenous fibers, which gradually develop into scar tissue.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β can increase expression of collagen I/III by stimulating the synthesis and deposition of collagen, fibronectin, proteoglycan and other intercellular substances. Over-expression of TGF-β has been demonstrated to be a common pathway for different pathological factors leading to myocardial fibrosis [ 12 - 14 ]. Another pro-fibrotic gene, β-catenin has been demonstrated to have crosstalk with TGF-β, [ 11 , 15 , 16 ] which is complex and context-dependent, [ 16 ] while our previous study demonstrated that fractalkine (FKN) plays an important role in the promotion of myocardial fibrosis and cardiac remodeling via up-regulating matrix metallopeptidase 9, procollagen I and III, and TGF-β.…”
Section: Introductionmentioning
confidence: 99%
“…Он оказывает стимулирую щее действие на клетки мезенхимального происхожде ния (фибробласты, тучные клетки, адипоциты) и облада ет ингибирующим действием на клетки эпителиальной (эндотелий) и нейроэктодермальной природы. У обсле дованных нами пациентов с ГКМП выявлен повышен ный уровень TGFβ1, что согласуется с ранее опублико ванным исследованием, в котором повышенный уровнь TGFβ1 имели пациенты с ГКМП с более высоким ФК СН, более высоким уровнем натрийуретического пепти да и более частыми повторными госпитализациями [8]. Таким образом, повышенный уровень TGFβ1 может служить прогностическим фактором неблагоприятных событий у пациентов с ГКМП.…”
Section: Discussionunclassified